Donor and transplant candidate selection for solid organ transplantation during the COVID‐19 pandemic. Issue 11 (15th July 2020) - Galvan, N. Thao N.; Moreno, Nicolas F.; Garza, Jay E.; Bourgeois, Susan; Hemmersbach‐Miller, Marion; Murthy, Bhamidipati; Timmins, Katherine; O'Mahony, Christine A.; Anton, James; Civitello, Andrew; Garcha, Puneet; Loor, Gabe; et al.
Abstract : Severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2), a novel coronavirus responsible for a worldwide pandemic has forced drastic changes in medical practice in an alarmingly short period of time. Caregivers must modify their strategies as well as optimize the utilization of resources to ensure public and patient safety. For organ transplantation, in particular, the loss of lifesaving organs for transplantation could lead to increased waitlist mortality. The priority is to select uninfected donors to transplant uninfected recipients while maintaining safety for health care systems in the backdrop of a virulent pandemic. We do not yet have a standard approach to evaluating donors and recipients with possible SARS‐CoV‐2 infection. Our current communication shares a protocol for donor and transplant recipient selection during the coronavirus disease 2019 (COVID‐19) pandemic to continue lifesaving solid organ transplantation for heart, lung, liver, and kidney recipients. The initial results using this protocol are presented here and meant to encourage dialogue between providers, offering ideas to improve safety in solid organ transplantation with limited health care resources. This protocol was created utilizing the guidelines of various organizations and from the clinical experience of the authors and will continue to evolve as more is understood about SARS‐CoV‐2 and how it affects organ donors and transplant recipients. Abstract : The authors devise an algorithm using donor and recipient exposure and clinical risk factors to avoid transplanting SARS‐CoV‐2–positive organs or SARS‐CoV‐2–positive transplant candidates.